Improving English Vocabulary Mastering using A Games of Cross Puzzles in Class VIII at Students of SMPN 1 Kayangan in Academic Year 2022/2023 - Wahab, Abdul; Putraidi, Karyawan (PENA : Jurnal Pendidikan Bahasa, Sastra, & Pengajaran, 2022)
The purpose of this study is to find out vocabulary exercises by using crossword puzzles. The method used in this research is classroom action research (CAR). The subjects in this study were Grade VIII students of SMPN 1 Kayangan, North Lombok Regency. The problem solving framework in this study is formulated in several implementation methods, namely as follows. (1). The initial stage will begin with observing the potential of SMPN 1 Kayangan students, North Lombok Regency, North Lombok Regency. This observation is carried out by attending events held by this community to obtain the necessary data. (2). In the second phase, the research team will prepare various materials related to vocabulary practice using crossword puzzles. These materials are adapted to the experiences and heterogeneity of students at SMPN 1 Kayangan, North Lombok Regency, North Lombok Regency. (3). The final stage is implementation. The results of this study were that almost all participants were enthusiastic and felt the benefits of this training. The implementation of the research for students of SMPN 1 Kayangan, North Lombok Regency can be concluded that it was successful up to the training stage in mastering vocabulary using crossword puzzles. This success was shown, among other things, by: (1) the suitability of the material with the needs of students at SMPN 1 Kayangan, North Lombok Regency in improving their ability to master vocabulary. (2) there was a positive response from the participants considering that research activities were students' needs in order to improve their English skills, and (3) the majority (90%) of the participants had understood the concept of crossword games in improving their ability to master vocabulary so that they were successfully published in national journals.